2012
DOI: 10.1111/j.1537-2995.2012.03767.x
|View full text |Cite
|
Sign up to set email alerts
|

Donor performance of combat readiness skills of special forces soldiers are maintained immediately after whole blood donation

Abstract: This study supports the fact that buddy transfusion may be feasible for healthy well-trained soldiers and does not decrease donor combat performance under ideal circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 17 publications
0
42
0
Order By: Relevance
“…Finally, the soldiers placed a sternal intraosseous device and reinfused the FWB. Physical fitness and marksmanship were unaffected by the phlebotomy, all soldiers were able to perform phlebotomy and all were able to place the intraosseous device [48].…”
Section: Hospital Treatmentmentioning
confidence: 99%
“…Finally, the soldiers placed a sternal intraosseous device and reinfused the FWB. Physical fitness and marksmanship were unaffected by the phlebotomy, all soldiers were able to perform phlebotomy and all were able to place the intraosseous device [48].…”
Section: Hospital Treatmentmentioning
confidence: 99%
“…The Norwegian Naval Special Operation Commandos have shown, in experimental conditions, that buddy transfusion is feasible, safe for the donor and does not decrease donor combat performance in ideal circumstances in simulated combat 93. Thus, they have developed a training programme and have shown the feasibility of the collection of fresh whole blood by specifically trained medics 89…”
Section: Far-forward Blood Transfusionmentioning
confidence: 99%
“…However, there are some concerns about the pertinence of lactate levels for the evaluation of shock severity during combat. Lactate levels rise naturally when significant exercise is performed, and levels as high as 12 mmol/L can be observed in combat scenarios 93. To overcome this limitation, in the case of doubt, it is suggested that lactate capillary levels should be measured a second time, 15–20 min later, in order to establish a trend line.…”
Section: Protocol Proposalmentioning
confidence: 99%
“…Making WFWB available in the farforward environment became one of their main goals, and postdonation performance had to be evaluated before a protocol could be implemented. Researchers linked to the Naval Special Operation Forces (SOF) community designed and completed two studies examining this subject (24). The parameters of oxygen uptake, shooting skills for cognitive purposes, and mountain hiking were investigated.…”
Section: In-the-field Issuesmentioning
confidence: 99%